Public Registries as Tools for Realising the Swedish Welfare State – Can the State still Be Trusted? - Reichel, Jane; Chamberlain, Johanna (Public Governance, Administration and Finances Law Review, 2022)
Sweden has a long tradition of transparency and keeping public archives and registries for the benefit of the society at large. Access to comprehensive public information, including registries with containing individualised data, has been an integral part in the building of the Swedish welfare state. An important explanatory factor for the acceptance of is the high level of social trust in the Swedish society, in that citizens to a large extent trust each other, the government and the public authorities and other institutions in the society. Over the last few decades, changes have taken place connected to digitalisation of the society and an increased awareness of the possible privacy intrusion that may follow. A number of Swedish “register scandals” have been unearthed in media, involving both private and public entities. In order to protect the Swedish cultural heritage of accessible archives and public information and retain social trust, the Swedish legislator should carefully balance the interest in transparency against the right to privacy and data protection following case law of the European Court of Human Rights and EU law.